KECERNAAN IN SACCO HIJAUAN LEGUMINOSA DAN HIJAUAN NON- LEGUMINOSA DALAM RUMEN SAPI PERANAKAN ONGOLE - Rendi Fathoni Hadi; Kustantinah (Kustantinah); Hari Hartadi (Faculty of Animal Science, Universitas Gadjah Mada, 2011)
This study was aimed to explore the optimum potential of forage and the degradation rate the rumen of nutrient of forage (legume and non legume) derived different forage fodder used farmers. Seven forages i.e. Gliricidia (GL),Manilkara (SW), Sesbania (TP), Ficus (BR), Calothyrsus (KL), Jackfruit (NG), and Cacao leaves (CO), were used in this experiment. Samples were incubated in the rumen of fistulated cattle with different time intervals, namely 2, 4, 8,12, 16, 24, 36, and 48 hours. The collected data were the nutrient digestibility residues in rumen, including dried matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), and acid detergent fiber (ADF). Datawere analyzed using Completely Randomized Design (CRD). From the calculation of in sacco rumen, it was obtained the degradation theory (DT) values of DM : GL 60.06%; SW 34.78%; TP 73.96%; BR 41.40%; KL 43.80%; NG 43.67%; and CO 28.67%. From in sacco rumen calculation, it was obtained the DT values of OM : GL 59.13%; SW 32.74%; TP 73.07%; BR 42.83%; KL 44.18%; NG 45.04%; and CO 26.80%. Calculation of in sacco rumen showed the DT values of CP : GL 66.14%; SW 32.49%; TP 81.46%; BR 42.89%; KL 31.84%; NG 47.05%; and CO 29.46%. The calculation of in sacco rumen, it was obtained the DT values of NDF: GL 46.84%; SW 46.59%; TP 56.69%; BR 44.18%; KL 23.01%; NG 30.07%; and CO 55.43%. From the calculation of in sacco rumen, it was obtained the DTvalues of ADF: GL 61.27%; SW 43.95%; TP 56.53%; BR 40.11%; KL 21.08%; NG 44.66%; and CO 69.15%. There were significant differences (P<0.05) on the degradation of DM, OM, CP, NDF, and ADF. It is concluded that not all of legume has higher DT values of DM, OM, CP, NDF, and ADF fraction than non-legume. There is a tendency that the longer retention time in the rumen, the higher degradation rate.(Keywords: Legume, Non-legume, In sacco rumen)